Diagnosis of hyperfunctional thyroidn odules - Ruhlmann, M.; Stebner, V.; Görges, R.; Farahati, J.; Simon, D.; Bockisch, A.; Rosenbaum-Krumme, S.; Nagarajah, J. (Nuklearmedizin - NuclearMedicine, 2014)
Aim: Several studies described the ultrasound based real-time elastography (USE) having a high sensitivity, specificity and negative predictive value in the diagnosis of suspicious thyroid nodules. Recently published studies called these results into question. Until now the usefulness of USE in the diagnosis of scintigraphically hyperfunctional thyroid nodules is not examined. Patients, methods: This study included 135 hyperfunctional thyroid nodules of 102 consecutive patients. The following attributes of the nodules were analyzed: stiffness with the USE using scores of Rago or Asteria and ultrasound criteria using TIRADS. Results: 94 of the examined thyroid nodules (70%) were rated as hard (suspicious for malignancy) and 41 nodules (30%) as soft (not suspicious) with a specificity of 30%. The scoring systems of Rago and Asteria showed no sigificant difference. Applying the TIRADS criteria 44 nodules (33%) have a higher risk for malignancy (33 nodules TIRADS 4a, 11 nodules TIRADS 4b). Combining USE and TIRADS 32 nodules (24%) are categorized as suspicious (intersection of hard nodules that are categorized as TIRADS 4a or 4b). Conclusion: Ultrasound based real-time elastography cannot identify scintigraphically hyperfunctional thyroid nodules as benign nodules reliably. Its accuracy in the assessment of at least “hot” thyroid nodules is to be questioned.
Keywords: Thyroid nodules; elastography; thyroid ultrasound; thyroid scintigraphy; TIRADS; hyperthyroidism